The anticancer compound identification from chloroform extract of Rhizopora mucronata stem bark - Diastuti, Hartiwi; ., Warsinah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Previous reasearch reported that chloroform extract that was partitioned from etanol exctracts of R. mucronata stem bark had sitotoxic against Myeloma cells (Diastuti, 2008). This research was aimed to fractinate the chloroform extract of R. mucronata stem bark and cytotoxicity test againts Myeloma cells, then identification the cytotoxic compounds. The ethanol extracts of R. mucronata steam bark was partitioned with chloroform. The chloroform extracts was fractinated by coloum chromatography with gradient eluent were nhexane, chloroform, etilacetate and methanol respectivelly. Cytotoxicity test the fraction of chloroform extracts were conducted on Myeloma cells by MTT methods. Identification the compoud of fraction that had a highest cytotoxic againts Myeloma cells conducted using IR spectrometer, and GCMS. The result showed that 2b fraction of R. mucronata stem bark had a highest cytotoxic againts Myeloma cells, having IC50 equal to 5.122 µg/mL. Identification of chemical compounds showed that 2b fraction contained two steroid compounds were 4 methyl- colest-24-en-3-ol and 4-methyl-stigmast-22-en-3-ol.Key words : R. Mucronata, anticancer, Myeloma cells, steroids